Cyberbullying : a bully-centric intervention program. - Saw, Chun Yu. (2012)
Cyberbullying, an emerging trend of bullying in its unprecedented technological form, has fast become a social issue that warrants immediate intervention. However, current literature has offered mostly intervention strategies that focus on the treatment of the victims, rather than the rehabilitation of the cyberbullies. Such victim-centric intervention programs, while helpful, do not appear to be effective in tackling cyberbullying. This review provides an overview of the cyberbullying problem by focusing on its (a) definition; (b) modus operandi (i.e., method of operation); (c) perpetrators and (d) theories. These findings form the foundation for the recommendations of the bully-centric intervention program. The recommended intervention program serves to complement existing victim-centric interventions in effectively managing the cyberbullying problem. Finally, this review concludes by highlighting plausible limitations and future directions of the recommended intervention program.